Patch test results with the European baseline series and additions thereof in the ESSCA network, 2015‐2018. (7th October 2020) - Uter, Wolfgang; Bauer, Andrea; Belloni Fortina, Anna; Bircher, Andreas J.; Brans, Richard; Buhl, Timo; Cooper, Susan M.; Czarnecka‐Operacz, Magdalena; Dickel, Heinrich; Dugonik, Aleksandra; Geier, Johannes; Giménez‐Arnau, Ana M.; et al.
Abstract: Background: Clinical surveillance of the prevalence of contact allergy in consecutively patch tested patients is a proven instrument to continually assess the importance of contact allergens (haptens) assembled in a baseline series. Objectives: To present current results from the European Surveillance System on Contact Allergies, including 13 countries represented by 1 to 11 departments. Methods: Anonymized or pseudonymized patch test and clinical data from various data capture systems used locally or nationally as transferred to the Erlangen data centre were pooled and descriptively analysed after quality control. Results: In the 4 years (2015‐2018), data from 51 914 patients patch tested with the European baseline series (EBS) of contact allergens were analysed. Contact allergy to nickel was most frequent (17.6% positive), followed by contact allergy to fragrance mix I (6.9%), methylisothiazolinone (MI; 6.2%), and Myroxylon pereirae resin (balsam of Peru; 5.8%). Conclusions: While the prevalence of MI contact allergy decreased substantially following regulatory intervention, the persistently high levels of allergy to metals, fragrances, other preservatives, and rubber chemicals point to problems needing further research and, potentially, preventive efforts. Results with national additions to the baseline series provide important information on substances possibly to be considered for inclusion in the EBS.